Hypertension risk pathways in urban built environment: the case of Yuhui District, Bengbu City, China - Gu, Kangkang; Jing, Yao; Tang, Jingjing; Jia, Xianjie; Zhang, Xinmu; Wang, Beichen (Frontiers in Public Health, 2024)
Introduction The rapid development of urbanization has brought about changes in residents’ living environment and behavior, leading to health challenges such as hypertension. An improvement in the built-up environment in the community could contribute to the construction of a healthy city, promote the active life of the residents, and prevent and relieve hypertension. However, there is little research on the relationship between the built environment of the community and hypertension. This cross-sectional study aims to evaluate the relationship between communities’ built environment, health behavior, and hypertension grade of residents in Yuhui District of Bengbu City. Methods This study is based on data from the 2022 Health Survey of Residents in 21 communities. To investigate the impact of the community’s built environment on residents’ hypertension and the underlying mechanisms, regression and structural equation modeling were employed. Results and discussion The results show that the built environment of urban communities has a significant impact on the residents’ hypertension. The presence of high densities of supermarkets, convenience stores, parks and plazas, but low densities of clinics and hospitals, has been identified as a significant risk factor for the development of high blood pressure among the residents. Nevertheless, the adoption of healthy behaviors, including regular walking, physical activity, and a diet rich in fruit and vegetables, can play an important role in reducing the risk of hypertension. The findings of this study show that enhancements to the built environment in urban neighborhoods could contribute to a reduction in the prevalence of hypertension among residents. Furthermore, the implementation of efficacious health interventions in urban settings would facilitate the alteration of residents’ health behaviors and enhance their overall health status.